A thermal environment prediction method for a mine ventilation roadway based on a numerical method: A case study. (February 2023) - Xu, Yu; Li, Zijun; Li, Gang; Jalilinasrabady, Saeid; Zhai, Xiaowei; Chen, Yin; Wang, Bing
Abstract: Thermal environment prediction has become increasingly significant in recent years with its promise of wide application in underground structures. The current work presents a numerical method for the feasible and effective analysis of the airflow and surrounding rock temperatures in ultralong mine ventilation roadways to understand their dynamic heat transfer. To reduce the modeling effort and computation time with satisfactory accuracy, the ventilation roadway is approximated as a one-dimensional (1D) line element. Still, the surrounding rock of the roadway remains three-dimensional (3D). An equivalent heat transfer coefficient calculates the dynamic heat transfer in the radial direction of the roadway. A case analysis of the Sanhejian coal mine ventilation roadways in China is performed, and a comparison between the simulated results and field measurements indicates that the predicted airflow temperature shows good agreement. The change in the underground thermal environment concerning ventilation time is systematically investigated in detail. The surrounding rock of the roadway adjusts the underground thermal environment through heat absorption or heat release, and the temperature distribution of the surrounding rock presents a "V" shape in winter and a "W" shape in summer. The self-compression of air contributes to a remarkable heat source for the increase in airflow temperature in the air intake shaft. A roadway with a low initial temperature of the surrounding rock after long-term ventilation can effectively cool the high-temperature airflow underground in early summer. The reduction in ventilation volume will increase the cooling degree of airflow by the surrounding rock in long-term ventilation roadways in summer. Still, the airflow will be heated more significantly in short-term ventilation roadways. In addition, the increase in the average annual ambient temperature will result in a linear rise in underground airflow temperature.